Zmieniamy siebie i wieś. Chłopskie społeczniczki z portfolio ziemianki okresu II Rzeczypospolitej - Kostrzewska, Ewelina (Zeszyty Wiejskie, 2016)
In the early twentieth century there appeared women with emancipatory aspirations among peasants. They were adopting standards proposed by representatives of landladies from intellectual elites. The process was continued in the interwar period when countrywomen’s acts, choices and different attitudes were being developed. Maria Karczewska, a landlady herself as she was, became interested in individual aspirations of those women and their biographies thus popularizing their image among the society. It could be perceived as a personal dimension of a broader process of traditional elites’ influence on a new peasant elite composed of women.